Flexible carbon nano net film material and preparation method thereof

By deforming the polymer solution in the electric field to form a porous mesh structure and optimizing the carbon fiber structure through bidirectional stretching carbonization technology, the existing carbon nanofiber membrane materials have been solved, and the high conductivity and flexibility of flexible carbon nanofiber membrane materials have been achieved.

CN119753891AActive Publication Date: 2025-04-04JIANGNAN UNIV

Patent Information

Application Number
CN202411791377.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-04
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing carbon nanofiber membrane materials have thick fiber diameters, poor connectivity between fibers and poor conductivity, which seriously limit their application.

Method used

Emulsified droplets of polymer solution are used to deform and phase separation in the electric field to form a porous mesh structure, and the molecular rearrangement and structural evolution of carbon fibers are optimized through bidirectional stretching carbonization technology to form an efficient conductive network.

Benefits of technology

A flexible two-dimensional carbon nanomembrane material with good connectivity between fibers has good conductivity and flexibility, solving the problem of poor conductivity of existing materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753891A_ABST
    Figure CN119753891A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible carbon nano net film material and a preparation method thereof, and belongs to the technical field of nanofiber electrode materials. The preparation method of the flexible carbon nano net film material comprises the following steps: dissolving a polymer in a solvent A to obtain a solution B; ultrasonically dispersing the solution B in a solvent C to obtain a net spraying emulsion; wherein the solution B and the solvent C are immiscible; and carrying out electrostatic net spraying on the net spraying emulsion to obtain a polymer nano net film, pre-oxidizing, applying longitudinal and transverse tension in a protective atmosphere, calcining, and cooling to obtain the flexible carbon nano net film material. The flexible carbon nano net film material has an efficient conductive network, shows excellent conductivity and flexibility, and is widely applied to the fields of wearable equipment, flexible sensors, energy storage equipment and biomedical equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanofiber electrode materials, and specifically relates to a flexible carbon nano-membrane material and a preparation method thereof. Background Art

[0002] Flexible electronic devices have received extensive attention in recent years in the fields of wearable devices, flexible sensors, energy storage devices (such as flexible supercapacitors and lithium-ion batteries), biomedical devices, etc. Carbon nanomaterials have the characteristics of light weight, conductivity, and adjustable structure, and have important research and application value for the development of flexible electronic devices with light weight and high capacity. However, when nanocarbon materials (including quantum dots, carbon nanotubes, graphene, etc.) are assembled into macroscopic materials, their conductivity is greatly reduced due to the lack of effective connection between nanomaterials.

[0003] In recent years, electrospun carbon nanofiber membranes have become an important research direction in the field of flexible electronics due to their high specific surface area, good conductivity, porous structure, mechanical stability and processability. However, the diameters of existing electrospun carbon nanofibers are all in the submicron scale (>200nm), which limits the further improvement of the specific surface area. In addition, these carbon fiber membrane materials are assembled by random deposition of one-dimensional carbon fibers, and lack good connectivity between fibers, which limits the improvement of their conductivity (conductivity <130S / cm). Therefore, it is urgent to develop two-dimensional carbon nanofiber membrane materials with good interconnection structure and macroscopic size between nanofibers.

[0004] Chinese patent CN106992288A discloses an antimony / carbon nanofiber flexible material and its preparation method and application. Specifically, soluble antimony salt and imidazole organic matter are dissolved in organic solvents respectively, and then added to NN-dimethylformamide solution of polyacrylonitrile to obtain a uniform electrospinning solution containing antimony nanoparticles. After electrospinning, pre-oxidation and carbonization, antimony / carbon nano flexible material is obtained. However, the carbon material of the invention inevitably introduces antimony nanoparticles, which limits the application scope of the carbon fiber material. In addition, the carbon material fibers still lack connectivity, which limits the improvement of its conductive properties.

[0005] Chinese patent CN111180727A discloses a method for preparing a flexible and dense carbon nanofiber membrane and its application, specifically, a polymer and a carbon source are dissolved in a solvent to obtain a uniform and stable precursor solution, and the precursor solution is subjected to electrostatic spinning, pre-oxidation, and carbonization to obtain a flexible and dense carbon nanofiber membrane. Although there are certain bonding points between the carbon fibers in the membrane, the mechanical stability of the point-like connection structure is poor. In addition, the fibers are all at a submicron scale (~200nm), which limits the further improvement of the specific surface area.

[0006] Therefore, there is an urgent need to develop flexible two-dimensional carbon nanomesh membranes with good inter-fiber continuity without introducing oxide nanoparticles. Summary of the invention

[0007] [Technical issues]

[0008] The existing carbon nanofiber membrane materials have coarse fiber diameters, poor inter-fiber connectivity, and poor electrical conductivity, which severely limits their applications.

[0009] [Technical solution]

[0010] In order to solve the above technical problems, the purpose of the present invention is to provide a flexible carbon nanomesh material and a preparation method thereof. The carbon nanomesh material has good conductivity and flexibility, and effectively solves the problems of coarse fiber diameter, poor fiber connectivity and poor conductivity in existing carbon nanofiber membrane materials.

[0011] In order to achieve the above purpose, the technical solutions provided are as follows:

[0012] The present invention provides a method for preparing a flexible carbon nano-membrane material, the preparation method comprising the following steps:

[0013] (1) dissolving the polymer in solvent A to obtain solution B;

[0014] (2) ultrasonically dispersing the solution B obtained in step (1) in the solvent C to obtain a spunlace emulsion; wherein the solution B and the solvent C are immiscible;

[0015] (3) electrostatically spraying the spunlace emulsion obtained in step (2) to obtain a polymer nanomembrane;

[0016] (4) Pre-oxidizing the polymer nanomembrane obtained in step (3), applying longitudinal and transverse tensions, calcining, and cooling the polymer nanomembrane under a protective atmosphere to obtain a flexible carbon nanomembrane material.

[0017] In one embodiment, the polymer in step (1) is at least one of polyacrylonitrile, polyethylene terephthalate, polyimide, polyaromatic polyamide, phenolic resin, polyethylene, polystyrene, polyurethane, or a mixture of any two or three of the above polymers.

[0018] In one embodiment, the molecular weight of polyacrylonitrile is 10,000-1,000,000; the molecular weight of polyethylene terephthalate is 20,000-50,000; the molecular weight of polyimide is 50,000-100,000; the molecular weight of polyaromatic polyamide is 50,000-150,000; the molecular weight of phenolic resin is 500-5,000; the molecular weight of polyethylene is 100,000-400,000; the molecular weight of polystyrene is 250,000-700,000; and the molecular weight of polyurethane is 50,000-150,000.

[0019] In one embodiment, the solvent A in step (1) is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, ethanol, chloroform, dichloromethane, and methyl pyrrolidone, or a mixture of several thereof.

[0020] In one embodiment, the mass fraction of the polymer in the solution B in step (1) is 5-20%.

[0021] In one embodiment, the ultrasonic power in step (2) is 500-2500w.

[0022] In one embodiment, the particle size of the spunlace emulsion in step (2) is 10 to 100 nm.

[0023] In one embodiment, the solvent C in step (2) is one or more of carbon tetrachloride, carbon tetrafluoride, n-hexane, cyclohexane, isobutane, n-butane, heptane, n-dodecane, n-tetradecane, hexadecane, and petroleum ether.

[0024] In one embodiment, the mass ratio of the solution B to the solvent C in step (2) is 1:99 to 20:80.

[0025] In one embodiment, the parameters of the electrostatic spraying in step (3) are: temperature 10-30°C, relative humidity 20%-70%, infusion speed 0.1-30mL / h, voltage 5-60kV, distance between the receiving device and the spinneret 10-30cm, slide distance 1-10cm, and the receiving device is a metal roller.

[0026] In one embodiment, the pre-oxidation process in step (4) is: in a muffle furnace, under an air atmosphere, heating to 150°C to 300°C at a heating rate of 1 to 5°C / min, and keeping warm for 0.5 to 2h.

[0027] In one embodiment, the protective atmosphere in step (4) is at least one of argon or nitrogen.

[0028] In one embodiment, the application of longitudinal and transverse tensions in step (4) is to place the nanomembrane in a tubular furnace with longitudinal and transverse bidirectional stretching functions, the longitudinal stretching tension is 1-20 MPa, and the transverse stretching tension is 1-20 MPa.

[0029] In one embodiment, the calcination temperature in step (4) is increased to 450°C to 600°C at a heating rate of 2 to 10°C / min and kept at that temperature for 3 to 6 hours, then increased to 900 to 1200°C at a heating rate of 2 to 5°C / min and kept at that temperature for 1 hour to 4 hours, and finally slowly cooled in the furnace.

[0030] The present invention also provides a flexible carbon nano-membrane material obtained by the above-mentioned preparation method.

[0031] The present invention also provides applications of the above-mentioned flexible carbon nanomesh material in the fields of wearable devices, flexible sensors, energy storage devices and biomedical devices.

[0032] Beneficial effects:

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1. The present invention utilizes the deformation and phase separation of the emulsified droplets of the polymer solution in an electric field to form a highly stable porous network structure. This method has good universality and can be applied on a large scale;

[0035] 2. The present invention utilizes biaxial stretching carbonization technology to optimize the molecular rearrangement and structural evolution of carbon fibers during heat treatment, thereby avoiding cracks and defects in the carbon fibers when the temperature rises rapidly, reducing the formation of micropores, and contributing to the structural consistency of the fibers in the nanonet, thereby forming a more efficient conductive network, thereby making the material have good conductive properties and flexibility;

[0036] 3. The fiber network formed by the present invention using emulsion electrospraying technology has a significant hierarchical channel structure and good connectivity between fibers. This structure reduces the problem of lack of good connectivity between fibers due to random deposition and assembly of fibers in traditional nanofiber membranes, and helps to efficiently transmit electrons in nanonet membranes. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The SEM images of the nanomembranes of Examples 1-4 of the present invention; (a) is Example 1; (b) is Example 2; (c) is Example 3; (d) is Example 4;

[0038] Figure 2 The SEM images of the products prepared in Comparative Example 1 and Comparative Examples 3-4 are as follows; (a) is Comparative Example 1; (b) is Comparative Example 3; and (c) is Comparative Example 4. DETAILED DESCRIPTION

[0039] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention. The following specific implementation methods further describe the present invention.

[0040] Example 1

[0041] A method for preparing a flexible carbon nanomembrane material comprises the following steps:

[0042] (1) adding polyacrylonitrile with a molecular weight of 90,000 to an N,N-dimethylformamide solvent, wherein the mass percentage of the polyacrylonitrile is 12 wt %, and fully dissolving the polyacrylonitrile to prepare a uniform solution A;

[0043] (2) adding solution A to n-hexane solvent, wherein the mass ratio of solution A to n-hexane is 1:4, and ultrasonicating with an ultrasonic machine with a power of 800 W until solution A is completely emulsified and the particle size is 10 to 100 nm, thereby obtaining a spunlace emulsion;

[0044] (3) Under the conditions of humidity of 45% and ambient temperature of 27° C., the spunlace emulsion was added to an electrospinning device, and electrospinning was performed under the conditions of static voltage of 20 kV, injection pump flow rate of 0.5 mL / h, and fiber receiving distance of 20 cm to obtain a polyacrylonitrile nanomembrane;

[0045] (4) The polyacrylonitrile nanomembrane is pre-oxidized in a muffle furnace, and the temperature is increased to 240°C at a heating rate of 5°C / min in an air atmosphere, and the temperature is kept at this temperature for 1 hour. The pre-oxidized fiber membrane is then placed in a tubular furnace, and the longitudinal stretching tension of the nanomembrane is 2 MPa, and the transverse stretching tension is 2 MPa in a nitrogen atmosphere. The calcination temperature is increased to 450°C at a heating rate of 10°C / min and kept at this temperature for 3 hours, and then increased to 1200°C at a heating rate of 5°C / min and kept at this temperature for 1 hour. Finally, the flexible carbon nanomembrane material is slowly cooled in the furnace to obtain the flexible carbon nanomembrane material.

[0046] Example 2

[0047] A method for preparing a flexible carbon nanomembrane material comprises the following steps:

[0048] (1) adding polystyrene with a molecular weight of 520,000 to N,N-dimethylformamide to dissolve the polystyrene in an amount of 10 wt %, so that the polystyrene is fully dissolved to prepare a uniform solution A;

[0049] (2) adding solution A to hexadecane solvent, wherein the mass ratio of solution A to hexadecane is 1:9, and ultrasonicating with a 900 W ultrasonic machine until solution A is completely emulsified and the particle size is 10 to 100 nm, thereby obtaining a spunlace emulsion;

[0050] (3) under the conditions of humidity of 45% and ambient temperature of 25° C., the spunlace emulsion was added into an electrospinning device, and electrospinning was performed under the conditions of static voltage of 30 kV, injection pump flow rate of 1 mL / h, and fiber receiving distance of 15 cm to obtain a polystyrene nanomembrane;

[0051] (4) The polystyrene nanomembrane is pre-oxidized in a muffle furnace, heated to 300°C at a heating rate of 3°C / min in an air atmosphere, and kept warm for 2 hours; then the pre-oxidized fiber membrane is placed in a tubular furnace, in a nitrogen atmosphere, the longitudinal stretching tension of the nanomembrane is 4 MPa, the transverse stretching tension is 4 MPa, the calcination temperature is heated to 550°C at a heating rate of 5°C / min and kept warm for 3 hours, then heated to 1100°C at a heating rate of 5°C / min and kept warm for 1 hour, and finally slowly cooled with the furnace to obtain a flexible carbon nanomembrane material.

[0052] Example 3

[0053] A method for preparing a flexible carbon nanomembrane material comprises the following steps:

[0054] (1) adding polyimide with a molecular weight of 80,000 to dimethyl sulfoxide to dissolve the polyimide, wherein the mass percentage of the polyimide is 10 wt %, and fully dissolving the polyimide to prepare a uniform solution A;

[0055] (2) adding solution A to petroleum ether solvent, wherein the mass ratio of solution A to petroleum ether is 1:4, and ultrasonicating with an 800W ultrasonic machine until solution A is completely emulsified and the particle size is 10 to 100 nm, thereby obtaining a spunlace emulsion;

[0056] (3) adding the spunlace emulsion to an electrospinning device under the conditions of a humidity of 50% and an ambient temperature of 23° C., and performing electrospinning under the conditions of an electrostatic voltage of 25 kV, a syringe pump flow rate of 1.5 m / h, and a fiber receiving distance of 20 cm to obtain a polyimide nanomembrane;

[0057] (4) The polyimide nanomembrane is pre-oxidized in a muffle furnace, and the temperature is increased to 200°C at a heating rate of 2°C / min under air atmosphere, and kept warm for 1.5 hours; then the pre-oxidized fiber membrane is placed in a tubular furnace, and the longitudinal stretching tension of the nanomembrane is 4 MPa, the transverse stretching tension is 4 MPa, the calcination temperature is increased to 550°C at a heating rate of 8°C / min and kept warm for 4 hours, and then increased to 1200°C at a heating rate of 5°C / min and kept warm for 1 hour, and finally slowly cooled in the furnace to obtain a flexible carbon nanomembrane material.

[0058] Example 4

[0059] A method for preparing a flexible carbon nanomembrane material comprises the following steps:

[0060] (1) adding a polyurethane with a molecular weight of 80,000 to N,N-dimethylacetamide to dissolve the polyurethane, wherein the mass percentage of the polyurethane is 10 wt %, and fully dissolving the polyurethane to prepare a uniform solution A;

[0061] (2) adding solution A to carbon tetrachloride solvent, wherein the mass ratio of solution A to carbon tetrachloride is 1:3, and ultrasonicating with a 1000W ultrasonic machine until solution A is completely emulsified and the particle size is 10 to 100 nm, thereby obtaining a spunlace emulsion;

[0062] (3) adding the spunlace emulsion to an electrospinning device under the conditions of a humidity of 40% and an ambient temperature of 25° C., and performing electrospinning under the conditions of an electrostatic voltage of 20 kV, a syringe pump flow rate of 1 m / h, and a fiber receiving distance of 25 cm to obtain a polyurethane nanomesh;

[0063] (4) The polyurethane nanomembrane is pre-oxidized in a muffle furnace, heated to 250°C at a heating rate of 3°C / min, and kept warm for 2 hours; then the pre-oxidized nanofiber mesh is placed in a tubular furnace, and in a nitrogen atmosphere, the longitudinal stretching tension of the nanofiber mesh is 6 MPa, the transverse stretching tension is 6 MPa, the calcination temperature is heated to 500°C at a heating rate of 5°C / min and kept warm for 5 hours, then heated to 1100°C at a heating rate of 2°C / min and kept warm for 1 hour, and finally slowly cooled with the furnace to obtain a flexible carbon nanomembrane material.

[0064] Comparative Example 1

[0065] The only difference from Example 1 is that in step (2), solution A is added to n-hexane solvent, and is not subjected to ultrasonic dispersion but only to physical stirring, and the obtained particle size is 7 to 12 mm. Other parameters and conditions are the same as those in Example 1.

[0066] The SEM image of the product prepared in this comparative example is as follows Figure 2 As shown in a:

[0067] Depend on Figure 2 It can be seen that compared with Example 1, the sample finally obtained in Comparative Example 1 only has nanofibers, and no nanomesh is formed. This is mainly because the polymer droplets cannot be dispersed into nanosize only under physical stirring, and larger droplets are difficult to overcome surface tension in the electric field to form a nanomesh film, and can only form a nanofiber film.

[0068] Comparative Example 2

[0069] The only difference from Example 1 is that in step (4), no longitudinal or transverse tension is applied to the pre-oxidized polyacrylonitrile nanomembrane during the carbonization process, and other parameters and conditions are the same as those in Example 1.

[0070] The product prepared in this comparative example has poor mechanical properties, is fragile and brittle, and its bending stiffness is difficult to measure.

[0071] Comparative Example 3

[0072] The only difference from Example 1 is that in step (2), solution A is added to N,N-dimethylacetamide, and the other parameters and conditions are the same as those in Example 1.

[0073] The SEM image of the product prepared in this comparative example is as follows Figure 2 As shown in b. Figure 2 b It can be seen that: compared with Example 1, the sample finally obtained in Comparative Example 3 only has microspheres and short nanofibers, and no nanonet is formed. This is mainly because N,N-dimethylacetamide and N,N-dimethylformamide are miscible, resulting in low viscosity of the polyacrylonitrile solution and insufficient entanglement of the molecular chains.

[0074] The product prepared in this comparative example is difficult to be self-supporting, is easily broken and brittle, and its bending rigidity is difficult to measure.

[0075] Comparative Example 4

[0076] The only difference from Example 1 is that step (2) is directly omitted and uniform solution A is used for preparation. Other parameters and conditions are the same as those in Example 1.

[0077] The SEM image of the product prepared in this comparative example is as follows Figure 2 As shown in c.

[0078] Depend on Figure 2 c It can be seen that: compared with Example 1, the sample finally obtained in Comparative Example 4 only has continuous nanofibers, and no nanonet is formed. This is mainly because Solution A is a uniform polymer solution, the viscosity of the solution is moderate, and the molecular chains have certain entanglement.

[0079] Performance Testing

[0080] 1. Carbon nanomembrane conductivity test

[0081] The conductivity of the prepared flexible carbon nanomesh material was tested using a ST-2258C four-probe tester. First, the thickness and shape of the flexible carbon nanomesh material sample were corrected, and then the sample was placed flat on the test bench and its forward and reverse conductivity was measured. Three points were randomly selected for each sample for testing, and the average value was taken as its conductivity, in S / cm.

[0082] 2. Carbon nanomembrane flexibility test

[0083] The softness of the nanomembrane is tested according to the international standard ASTMD2923-01. A nanomembrane with an area of ​​10cm*10cm is placed flat on the upper end of the slit, and the axis of the membrane is aligned with the test slit on the instrument table. During the test, the stress sensing probe presses the fiber membrane vertically into the slit, and releases the pressure after reaching a certain depth. At this time, the softness tester automatically displays the bending stiffness of the nanomembrane in mN.

[0084] The results are shown in Table 1:

[0085] Table 1. Properties of materials prepared in Examples and Comparative Examples

[0086]

[0087] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.

Claims

1. A method for preparing a flexible carbon nanomembrane material, characterized in that: The preparation method comprises the following steps: (1) dissolving the polymer in solvent A to obtain solution B; (2) ultrasonically dispersing the solution B obtained in step (1) in the solvent C to obtain a spunlace emulsion; wherein the solution B and the solvent C are immiscible; (3) electrostatically spraying the spunlace emulsion obtained in step (2) to obtain a polymer nanomembrane; (4) Pre-oxidizing the polymer nanomembrane obtained in step (3), applying longitudinal and transverse tensions, calcining, and cooling the polymer nanomembrane under a protective atmosphere to obtain a flexible carbon nanomembrane material.

2. The preparation method according to claim 1, characterized in that: The polymer in step (1) is at least one of polyacrylonitrile, polyethylene terephthalate, polyimide, polyaromatic polyamide, phenolic resin, polyethylene, polystyrene, polyurethane, or a mixture of any two or three of the above polymers.

3. The preparation method according to claim 1, characterized in that: The solvent A in step (1) is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, ethanol, chloroform, dichloromethane and methyl pyrrolidone, or a mixture of several of them.

4. The preparation method according to claim 1, characterized in that: The ultrasonic power in step (2) is 500-2500w.

5. The preparation method according to claim 1, characterized in that: The particle size of the spunlace emulsion in step (2) is 10 to 100 nm.

6. The preparation method according to claim 1, characterized in that: The solvent C in step (2) is one or more of carbon tetrachloride, carbon tetrafluoride, n-hexane, cyclohexane, isobutane, n-butane, heptane, n-dodecane, n-tetradecane, hexadecane and petroleum ether.

7. The preparation method according to claim 1, characterized in that: The parameters of the electrostatic spraying in step (3) are: temperature 10-30°C, relative humidity 20%-70%, infusion speed 0.1-30mL / h, voltage 5-60kV, distance between the receiving device and the spinneret 10-30cm, slide distance 1-10cm, and the receiving device is a metal roller.

8. The preparation method according to claim 1, characterized in that: The step (4) of applying longitudinal and transverse tensions is to place the nano web in a tubular furnace with longitudinal and transverse bidirectional stretching functions, wherein the longitudinal stretching tension is 1-20 MPa and the transverse stretching tension is 1-20 MPa.

9. The flexible carbon nanomembrane material obtained by the preparation method according to any one of claims 1 to 8.

10. Application of the flexible carbon nanomembrane material according to claim 9 in the fields of wearable devices, flexible sensors, energy storage devices and biomedical devices.

Citation Information

Patent Citations

  • Antimony / carbon nano-fiber flexible material, preparation method thereof and application

    CN106992288A

  • Preparation method and application of flexible compact carbon nano carbon fiber membrane

    CN111180727A

  • Method for preparing polyacrylonitrile-based carbon nanofiber precursor

    CN102102233A

  • Preparation method of cyano-modified polyacrylonitrile-based carbon fiber membrane

    CN112011896A

  • Composite fiber and manufacturing method therefor

    JP2017115280A

Cited By

  • Polymer nano net film and application thereof in oil product water removal

    CN119607625A

  • A polymer nanomembrane and its application in oil dewatering

    CN119607625B